Optimization of Artemisia ordosica crude polysaccharides on milk fatty acid composition in lactating donkeys and their effects on rectal microbiome and lactation performance - Meng, Fanzhu; Zhao, Yanli; Guo, Yongmei; Guo, Xiaoyu; Zhang, Qingyue; Li, Shuyi; Chi, Yue; Li, Li; Hui, Fang; Tong, Manman; Yan, Sumei (Frontiers in Microbiology, 2025)
IntroductionThis study evaluated the effects of dietary Artemisia ordosica crude polysaccharides (AOCP; 0.5 g/kg DM) supplementation on milk fatty acid profiles, rectal microbiota, enzymes related to lipid metabolism, and lactation performance in lactating Dezhou donkeys.MethodsA single-factor completely randomized design was used, with 14 lactating Dezhou donkeys (6.16 ± 0.67 years old, 250.06 ± 25.18 kg, parity 2.82 ± 0.48, 39.11 ± 7.42 days in lactation, each with a foal) randomly divided into two groups (n = 7/group). The CON group was fed a diet with a concentrate to forage ratio of 3:7, while the AOCP group received the same diet supplemented with 0.5 g/kg DM of AOCP. The trial lasted 10 weeks (including a 2-week adaptation period).Results and discussionCompared with the CON group, AOCP supplementation significantly enhanced lactation performance (milk yield, fat, lactose) and the digestibility of DM, ADF, NDF, and elevated oleic acid, linoleic acid, eicosapentaenoic acid, as well as the unsaturated-to-saturated (U/S) and polyunsaturated-to-saturated (P/S) fatty acid ratios, while reducing saturated fatty acids and the c index. AOCP elevated acetate and butyrate in the rectum and the activity of enzymes related to lipid metabolism such as stearoyl-CoA desaturase, and increased the relative abundance of beneficial bacteria (Eubacterium hallii group, Prevotella, Ruminococcus), while decreasing potentially pathogenic bacteria Streptococcus and norank_f_Lachnospiraceae. In summary, AOCP may optimize the fatty acid composition of donkey milk and enhance lactation performance by modulating rectal bacteria structure, enzymes related to lipid metabolism, and nutrient utilization.